Mustahik Economic Empowerment through Micro Business Development - Zaenal Alim Adiwijaya; Farikha Amilahaq (Jurnal Ilmiah Ekonomi Islam, 2023)
This research aims to develop an efficient model of economic empowerment through a micro business development program for mustahiq. The model development involves (1) providing capital through financing, 2) providing management skill training, (3) innovation development, 4) intensive assistance from BAZNAS, and 5) marketing strategy training. Those models are to improve the performance of micro-businesses so that mustahiq can be empowered. The effectiveness of the five variables was tested through multiple regression analysis using SPSS. The data is processed based on data tabulation of 78 selected respondents. The results show that providing capital from zakat productive, procuring management skill training, innovation development training, intensive assistance from amil zakat, as well as marketing strategy training, can improve the performance of mustahiq micro businesses. The business assistance and various training that accompanies the distribution of business capital, is a unified business incubation model to empower the mustahiq economy and is a characteristic of amil institutions compared to profit-oriented capital-providing institutions such as banks.